If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7 + -1x)(6 + -1x) = 0 Multiply (7 + -1x) * (6 + -1x) (7(6 + -1x) + -1x * (6 + -1x)) = 0 ((6 * 7 + -1x * 7) + -1x * (6 + -1x)) = 0 ((42 + -7x) + -1x * (6 + -1x)) = 0 (42 + -7x + (6 * -1x + -1x * -1x)) = 0 (42 + -7x + (-6x + 1x2)) = 0 Combine like terms: -7x + -6x = -13x (42 + -13x + 1x2) = 0 Solving 42 + -13x + 1x2 = 0 Solving for variable 'x'. Factor a trinomial. (6 + -1x)(7 + -1x) = 0Subproblem 1
Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6Subproblem 2
Set the factor '(7 + -1x)' equal to zero and attempt to solve: Simplifying 7 + -1x = 0 Solving 7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 0 + -7 -1x = 0 + -7 Combine like terms: 0 + -7 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7Solution
x = {6, 7}
| 9x-20+10x-5=3x-6x-15 | | .24g+14.8=16.24 | | F(x)=2x^2+7x-12 | | -9g=-9g+8 | | 3x+40=2x+20 | | 1/3(x-9)1/8(3x-1) | | 4x^2-36x+72= | | 13i+7=2i-9 | | 594=18b+72 | | 2(x+2)=6x+1-4x+3 | | -6w+10=-10-8w | | x(5)=315 | | 2z+4z+2+z+10=z+2+20 | | 9y+5=15y+7 | | s^3+2s^2+12s-40=0 | | 120-80y=-3y+9 | | 4+4y+2=-2 | | 46/n=117 | | N^2-12n=32 | | 4a(5)3= | | 2x-5=2x+18 | | m-11=15-6b | | -6x+-6x= | | t=1.25h-10 | | -1-7x=36x+(-7-x) | | -6z+6=6-6z | | 0.2v=1.2 | | 2(y-1)+6y=10 | | 25-6x=-65 | | 7x-(3x+13)=23 | | 21-1/24(3)=14-1/24(2x) | | 1.1-t+2.2=5.9 |